Synthesis and Application of 2-Arylazo-10-(oxo)-perinaphtho[1,2-d]thiazole - Pawar, G.G.; Bineesh, P.; Kumar, P.S.R.; Rangnekar, D.W.; Kanetkar, V.R. (Asian Journal of Chemistry, 2016)
2-Amino-10-(oxo)-perinaphtho[1,2-d]thiazole was synthesized and utilized to prepare a range of azo disperse dyes (1a-f). These novel aryl azo dyes were studied with respect to their colour and constitutional relationship. Application properties of these dyes on polyester fabric and their fastness properties were evaluated. These dyes were characterized by IR, PMR and visible absorption spectra.